New Concept of Oxygen and Ozone Self-regulation in the Atmosphere and Low-temperature Interaction between Ozone and HCl Solutions; Regional Conference on Ozone Generation and Application to Water and Waste Water Treatment (ECWATECH-98), Moscow, 1998 - Zosimov A. V.; Lunin V. V.; Yagodovskaya T. V.; Levanov A. V.; Gromov A. R.; Shishnyayev V. I.; Pestryakov A. N. Aleksey Nikolaevich (1998, 1998)
В фонде НТБ ТПУ отсутствует